SISTEM PELAPORAN, KETAATAN PADA PERATURAN PERUNDANGAN DAN PENGANGGARAN BERBASIS KINERJA SERTA DAMPAKNYA TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Studi Survey Pada SKPD Kabupaten Brebes) - Wila Nur Rahmadani (AKT 16 UMY 340, 2016)
This study aims to examine the influence of The Reporting System, Legislation Compliance With Regulation, Performance Based Budget And The Impact Toward Performance Accountability Of Public Institution. In this study, were selected using purposive sampling that is not random sample selection is based on several criteria. Population in this study were all heads of agencies, secretarial services, superintendent, chief financial subpart, financial departemen staff, section head and staff of government agencies in the country Brebes, sample of 83 respondents This research was processed using SPSS program. The result that Reporting System not have a positive and significant influence on the Performance Accountability Of Public Institution. Legislation Compliance With Regulation, and Performance Based Budget have a positive and significant influence on the Performance Accountability Of Public Institution. This shows that the Reporting System have a negative on the the Performance Accountability Of Public Institution. This shows that the Legislation Compliance With Regulation, and Performance Based Budget have a positif on the Performance Accountability Of Public Institution .